ANALISIS PROSES PEMBELAJARAN BAHASA ARAB PADA TINGKAT TSANAWIYAH DI PONDOK PESANTREN TA’MIRUL ISLAM - Nurul Hidayatul Amalina; Muhammad Nashirudin (Jurnal Tatsqif, 2017)
The current research intends to describe about the implementation of teaching standard process in Arabic Language subject in Ta’mirul Islam Islamic Boarding School Surakarta consisting of (1) lesson preparation in Arabic Language consisting syllabus and lesson plan, (2) the teaching implementation in Arabic Language, and (3) the inhibit factors in Arabic Language teaching preparation and implementation including their alternative solutions. The current research is a qualitative descriptive. The data are collected through interview, observation, and documentation. Based on data analysis, the current research found that: 1) the syllabus used for language subjects are adapted from Pondok Modern Gontor. Meanwhile, lesson plans for Arabic Language subject are formulated by teachers themselves individually. It is found that the lesson plan formulations are not working optimally. 2) Teaching implementations are conducted standardized enough, such as the number of students, time allocation, textbooks, and teaching process. 3) one of the barrier factors for syllabus formulation is the lack of coordination among teachers about the scope of teaching materials. Teacher motivation and teacher time management are among two factors inhibit lesson plan formulations. Meanwhile, factors that inhibit the implementation of teaching processes such as lack of material review by teachers and monotonous teaching method affecting the attraction of teaching process. The recommended solution to overcome those barriers are making an endeavor to enhance teacher motivation and conducting class supervision.